CARACTERIZACIÓN DE LOS MATERIALES SEDIMENTARIOS INCONSOLIDADOS COSTEROS Y ALUVIALES ACTUALES EN LA REGIÓN DE PARRITA, PACÍFICO CENTRAL DE COSTA RICA - Cárdenes Sandí, Guaria (2011)
Two different sedimentary environments (alluvial and coastal setting) have been recognized inthe Parrita area. The continental environment is represented by alluvial facies (alluvial plains, active meandricchannels, active braided river channels, and paleomeandric channel facies), and small lacustrine deposits. Thecoastal environment is conformed by beach, sand bars, and estuarine facies. The beach facies are formed by theassign of the littoral currents (NW-SE), which carry out the sediment from the adjacent coast and may be fromthe inner platform. The sand bars and estuarine facies constitute a bar barrier system. This system is formed bya sequence of sand bars and swamps, which are colonized by "mangle" vegetation. The granulometriccharacteristics of sediments (mean, mode, sorting, skewness, kurtosis) typify every sedimentary facies.